CRYOPRESERVATION OF TRUE-SEED AND EMBRYO OF MAIZE AND SOYBEAN FOR LONG-TERM STORAGE - Enny Sudarmonowati; I. Fitryatmi; S. Sadjad (Indonesian Journal of Agricultural Science, 2001)
Study on cryopreservation of Indonesian local cultivars and improved  varieties of maize and soybean has never been done. This method may be used for long-term preservation of seeds of maize and soybean. In this study, the method was applied to maize and soybean, Arjuna and Wilis respectively, as a model for preserving germplasm of ortodox seeds. Whole seeds and excised embryos of both varieties were subjected to two methods of cryopreservation, i.e., two-stage cooling and rapid freezing with or without 15% dimethyl sulfoxide (DMSO) as cryoprotectant solution prior to immersion in liquid nitrogen (-196oC). Results indicated that there was no significant difference between the use of DMSO for both species in terms of viability, although pretreatment in DMSO was slightly reduced the percentage of viability of both species. Slow freezing to -30oC prior to immersion in the liquid nitrogen could give as high as 76.67% and 51.67% surviving whole seeds of maize and soybean, respectively. Preserving excised embryos of maize in the liquid nitrogen using either slow or rapid freezing significantly reduced the percentage of viability from 20-76.67% to 5-18.33% (four folds) depending on treatments applied. Results also showed that one day or 15 minutes of immersion of samples in the liquid nitrogen gave rise to similar values of viability of maize and soybean, i.e., 20-60% and 20-51.67%, respectively depending on  treatments applied. These results implied that for long-term storage of maize and soybean seeds as they could survive at the rate of 76.67% and 51.67% respectively, the seed can be treated by prefreezing to -30oCwithout the presence of DMSO prior to immersion in liquid nitrogen.